2021
DOI: 10.1038/s41392-021-00764-4
|View full text |Cite|
|
Sign up to set email alerts
|

Signaling pathways in the regulation of cytokine release syndrome in human diseases and intervention therapy

Abstract: Cytokine release syndrome (CRS) embodies a mixture of clinical manifestations, including elevated circulating cytokine levels, acute systemic inflammatory symptoms and secondary organ dysfunction, which was first described in the context of acute graft-versus-host disease after allogeneic hematopoietic stem-cell transplantation and was later observed in pandemics of influenza, SARS-CoV and COVID-19, immunotherapy of tumor, after chimeric antigen receptor T (CAR-T) therapy, and in monogenic disorders and autoim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 205 publications
2
24
0
Order By: Relevance
“…In this paper, we have presented three cases of patients with clinical manifestations that we can identify as belonging to CRS, and due to the neurological symptoms, to ICANS. Several pieces of evidence support the involvement of pro-inflammatory cytokines in the pathogenesis of CRS/ICANS, characterized by high levels of circulating pro-inflammatory cytokines, acute systemic inflammatory manifestations and secondary organ involvement [ 43 ]. In this context, our results have demonstrated that a cytokine blockade was able to relieve neurological manifestations in three patients who exhibited neuroinflammation associated with viral infections after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we have presented three cases of patients with clinical manifestations that we can identify as belonging to CRS, and due to the neurological symptoms, to ICANS. Several pieces of evidence support the involvement of pro-inflammatory cytokines in the pathogenesis of CRS/ICANS, characterized by high levels of circulating pro-inflammatory cytokines, acute systemic inflammatory manifestations and secondary organ involvement [ 43 ]. In this context, our results have demonstrated that a cytokine blockade was able to relieve neurological manifestations in three patients who exhibited neuroinflammation associated with viral infections after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, therapeutic targeting of TNF- α signaling has been extensively used for the treatment of several inflammatory diseases [ 26 , 27 ]. TNF- α can induce the expression of IL-6, IL-10, and IL-18, which can be used as an inflammatory marker for the development of sepsis [ 28 ]. Consistent with this previous study, our present study also revealed that the protective role of PNP in AKI was mediated through inhibition of inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“… 137 Cytokine release syndrome (CRS) could lead to multiorgan dysfunction, which can occur in COVID-19, and after chimeric antigen receptor T (CAR-T) therapy, which is clinically characterized high fever, hyperinflammation, and severe organ dysfunction. 138 According to the website clinicaltrials.gov there are currently at least 16 clinical trials ongoing to assess the efficacy of blocking IL-6R in COVID-19 patients with cytokine storm syndrome. 139 Tocilizumab, is used for rheumatic conditions and is also co-labelled by the US Food and Drug Administration (FDA) for treatment with CAR-T therapy, which might be repurposed for treatment for COVID-19.…”
Section: Methodsmentioning
confidence: 99%